Distinct Excitonic Circular Dichroism between Wurtzite and Zincblende CdSe Nanoplatelets - Gao, Xiaoqing; Zhang, Xiuwen; Zhao, Luyang; Huang, Pu; Han, Bing; Lv, Jiawei; Qiu, Xueying; Wei, Su-Huai; Tang, Zhiyong (Nano letters, 2018)
Nanocrystals (NCs) with identical components and sizes but different crystal structures could not be distinguished by conventional absorption and emission spectra. Herein, we find that circular dichroism (CD) spectroscopy can easily distinguish the CdSe nanoplatelets (NPLs) with different crystal structures of wurtzite (WZ) and zincblende (ZB) with the help of chiral l- or d-cysteine ligands. In particular, the CD signs of the first excitonic transitions in WZ and ZB NPLs capped by the same chiral cysteine are opposite. Theoretic calculation supports the viewpoint of different crystal structures and surfaces arrangements between WZ and ZB NPLs contributing to this significant phenomenon. The CD peaks appearing at the first excitonic transition band of WZ or ZB CdSe NPLs are clearly assigned to the different transition polarizations along 4p(x,y,z),Se → 5sCd or 4p(x,y),Se → 5sCd. This work not only provides a deep insight into the origin of the optical activity inside chiral semiconductor nanomaterials but also proposes the design principle of chiral semiconductor nanocrystals with high optic activity.